Antiproliferative activity of cardenolides on cell line A549: structure–activity relationship analysis - Meneses-Sagrero, Salvador Enrique; Rascón-Valenzuela, Luisa Alondra; Sotelo-Mundo, Rogerio; Vilegas, Wagner [UNESP]; Velazquez, Carlos; García-Ramos, Juan Carlos; Robles-Zepeda, Ramón Enrique (Springer Nature, 2020)
Abstract: Since the beginning, natural products have represented an important source of bioactive molecules for cancer treatment. Among them, cardenolides attract the attention of different research groups due to their cardiotonic and antitumor activity. The observed biological activity is closely related to their Na+/K+-ATPase inhibition potency. Currently, the discovery of new compounds against cancer is an urgent need in modern pharmaceutical research. Thus, the aim of this work is to determine the physicochemical properties and substituent effects that module the antiproliferative activity of cardenolides on the human lung cancer cell line A549. We build and curate a library with results obtained from literature; molecular descriptors were calculated in PaDEL software, and SAR/QSAR analysis was performed. The SAR results showed that cardenolides were sensitive to modifications in C and D steroidal ring and required substituent groups with the function of hydrogen bond acceptor at the C3 position. QSAR models to doubly linked-type cardenolides indicated that properties as lipoaffinity and atoms with the capacity to be hydrogen bond acceptors are involved in the increment of antiproliferative activity on A549 cell line. In contrast, the presence and position of very electro-negative atoms on the molecule decreased the antiproliferative effect on A549 cells. These results suggest that the antiproliferative capacity of cardenolides on the cell line A549 is strongly related to substituent groups on the C3 position, which must not be carbohydrate. Additionally, the steroidal rings C and D must remain without modifications. Graphic abstract: [Figure not available: see fulltext.].
Keywords: A549; Antiproliferative activity; Apocynaceae; Cardenolides; Lung tumor; SAR/QSAR